The influence of personal values and patient intoxication on nurses concerns about opioids: results of a prospective cross-sectional multi-centre study. Issue 1 (February 2021) - Heckroth, Antje; Pludra, Vanessa; Johannssen, Christian; Guest, Charlotte; Wiedermann, Frauke; Bantel, Carsten
Background: Nurses are the main administrators of opioids in hospitals and enjoy some autonomy when using them to manage pain. Nevertheless evidence suggests they exercise this freedom restrictively with the reasons for this self-limitation remaining unclear. Nurses are influenced by personal and professional values and by patients' attributes. Intoxicated patients pose a particular challenge. This study therefore investigated whether cautious attitudes towards opioids were aggravated in intoxicated patients and influenced by personal values. Methods: A two-version questionnaire was developed. Each presented a case vignette describing a patient in acute pain who was either intoxicated or not intoxicated. Questionnaires contained identical case statements inquiring about concerns regarding opioids, preferred analgesics and statements about opioids and personal values. They were distributed prospectively in a cross-sectional, multi-centre design. Equal distribution of both questionnaires was achieved through randomization of wards. Regression analysis was employed to determine predictors for responses to the case statements. Results: In total, n = 374 (26%) nurses returned questionnaires, 85% were female, 39% worked in surgery and 64% had >10 years experience. A total of 78% were concerned using opioids in the intoxicated patient and 70% preferred non-opioids instead. Most nurses agreed familiarity with an opioid gives them more confidence and they were more concerned in patients with a history of drug abuse. They neither associated opioids with helping patients to die nor with drug abuse. The majority endorsed value statements representing 'universalism', 'hedonism' and 'benevolence' while disagreeing with 'power' and 'stimulation'. Nurses concerns were predicted by values indicating 'conformity' and 'achievement'. Conclusion: Nurses were concerned giving opioids to intoxicated patients and preferred non-opioids instead. These concerns were predicted by personal values representing 'Conservation' ('conformity') and 'Self-Enhancement' ('achievement'). Therefore, stigmatizing mental models likely contribute to nurses' reluctance to use opioids. Interestingly, personal ambition might protect nurses from discriminatory thoughts and practice.